Antibacterial Effect of Aqueous and Alcoholic Extracts from Petal of Saffron (Crocus sativus L.) on some Foodborne Bacterial Pathogens - H Gandomi Nasrabadi; L Azami Sarokelaei; A Misaghi; S Abbaszadeh; N Shariatifar; N Tayyar Hashtjin (Institue of Medicinal Plants, ACECR, 2012)
Background: Health concerns due to adverse effects of chemical preservatives have increased public interest to consuming preservative-free products or product containing natural preservatives such as plant extract and their essential oils. Objective: In this study the antibacterial effect of aqueous, ethanolic and methanolic extracts from petal of saffron against the most important foodborne pathogens salmonella typhimurium, Listeria monocytogenes, E. coli O157: H7, Bacillus cereus and Staphylococcus aureus were evaluated. Methods: Disk diffusion method was done to screen bacterial sensitivity. The minimum inhibitory concentration (MIC) of extracts were evaluated by agar dilution and broth microdilution method Results: The most sensitive strain to extracts was S. typhimurium, and the most resistant strains were S. aureus and E. coli O157:H7. MICs of all extracts were estimated 40 mgml-1, against all bacteria using agar dilution method. The aqua and methanolic extracts showed antimicrobial activity against all of bacteria by broth microdilution and MIC estimated 40 mgml-1, however MIC of ethanolic extracts estimated 40 mgml-1 for L. monocytogenes, S. aureus and B. cereus, while the MICs for S. typhimurium and E. coli O157:H7 were estimated >40 mgml-1. Conclusion: The results of this study revealed that the studied extracts might be potential sources of natural antimicrobial agents, and propose their potential application in food system as a natural preservative.